An Approach to Characterizing the Spatial Pattern and Scale of Regional Heat Islands Over Urban Agglomerations. Issue 22 (18th November 2022) - Xie, Z. Q.; Du, Y.; Miao, Q.; Zhang, L. L.; Wang, N.
Abstract: Great difficulty in characterizing the spatial pattern and scale of regional surface urban heat islands (RSUHIs) over urban agglomerations is mainly attributed to the RSUHI extent exceeding urban boundaries and strong variations in the background climate state and land cover. A new method that successfully addresses these problems by applying the spatial similarity of the land surface temperature (LST) annual cycle in urban agglomerations is proposed to characterize the RSUHI spatial pattern and scale in the Yangtze River Delta of China. This method has good adaptability to complex terrain and climate variations and simultaneously identifies the RSUHI spatial pattern and scale. The RSUHI spatial extent averaged 3.7 × 10 4 km 2 in 2003–2020, which is 1.5–2.0 times the urban extent, and had a fluctuating but increasing tendency. Rapid urbanization and the spatial pattern‐shifting LST anomalies were mainly responsible for the fluctuating RSUHI extent during 2003–2020. Plain Language Summary: In contrast with a single city, urban agglomerations can create regional urban heat islands and threaten environmental sustainability, biodiversity, and resource and energy consumption on a regional scale. Accurately quantifying the spatiotemporal variations of regional urban heat islands is of practical importance to urban planning and environmental management in terms of shaping rational urban clusters, mitigating heat‐related health risks and improving human comfort in urban agglomerations. We propose a new method that reasonably identifies the urban–rural cliff of the land surface temperature in urban agglomerations using a spatial similarity algorithm, and we simultaneously identify the spatial pattern and scale of regional urban heat islands in the Yangtze River Delta of China. The proposed method has great potential in mitigating heat‐related health risks and improving urban design owing to its good adaptability to complex terrain, land cover and climate variations. Key Points: Rapid urbanization leads to strong differences in the annual cycle of the land surface temperature (LST) between urban and nonurban areas A new method based on the similarity of annual cycles of the LST is proposed to quantify regional heat island effects This method adapts well to complex terrain, land‐cover changes and climate variations and has great potential in urban planning